Axillary lymph node dissection versus no dissection in patients with T1N0 breast cancer: A randomized clinical trial (INT09/98). Issue 6 (5th December 2013) - Agresti, Roberto; Martelli, Gabriele; Sandri, Marco; Tagliabue, Elda; Carcangiu, Maria Luisa; Maugeri, Ilaria; Pellitteri, Cristina; Ferraris, Cristina; Capri, Giuseppe; Moliterni, Angela; Bianchi, Giulia; Mariani, Gabriella; et al.
Abstract : BACKGROUND: Although axillary surgery is still considered to be a fundamental part of the management of early breast cancer, it may no longer be necessary either as treatment or as a guide to adjuvant treatment. The authors conducted a single‐center randomized trial (INT09/98) to determine the impact of avoiding axillary surgery in patients with T1N0 breast cancer and planning chemotherapy based on biological factors of the primary tumor on long‐term disease control. METHODS: From June 1998 to June 2003, 565 patients aged 30 years to 65 years with T1N0 breast cancer were randomized to either quadrantectomy with (QUAD) or without (QU) axillary lymph node dissection; a total of 517 patients finally were evaluated. All patients received radiotherapy to the residual breast only. Chemotherapy for patients in the QUAD treatment arm was determined based on lymph node status, estrogen receptor status, and tumor grade. Chemotherapy for patients in the QU treatment arm was based on estrogen receptor status, tumor grade, and human epidermal growth factor receptor 2 and laminin receptor status. Overall survival (OS) was the primary endpoint. Disease‐free survival (DFS) and rate and time of axillary lymph node recurrence in the QU treatment arm were the secondary endpoints. RESULTS: After a median follow‐up of >10 years, the estimated adjusted hazards ratio of the QUAD versus QU treatment arms for OS was 1.09 (95% confidence interval, 0.59‐2.00; P  = .783) and was 1.04 (95% confidence interval, 0.56‐1.94; P  = .898) for DFS. Of the 245 patients in the QU treatment arm, 22 (9.0%) experienced axillary lymph node recurrence. The median time to axillary lymph node recurrence from breast surgery was 30.0 months (interquartile range, 24.2 months‐73.4 months). CONCLUSIONS: Patients with T1N0 breast cancer did not appear to benefit in terms of DFS and OS from immediate axillary lymph node dissection in the current randomized trial. The biological characteristics of the primary tumor appear adequate for guiding adjuvant treatment. Cancer 2014;120:885–893 . © 2013 American Cancer Society . Abstract : A 10‐year outcome study was performed in 517 women (mean age, 52.6 years [range, 30 years‐65 years]) with T1N0 breast cancer who were treated with conservative surgery and prospectively randomized to either axillary lymph node dissection or observation. Adjuvant treatment was based on biological factors of the primary tumor in the group of patients who received no axillary surgery. Overall survival and disease‐free survival did not appear to differ significantly between treatment arms, thereby indicating that axillary surgery may be avoided in these patients.